PERBANDINGAN BPW DENGAN NaCl FISIOLOGIS 0,9% SEBAGAI LARUTAN PENGENCER TERHADAP TPC SUSU SAPI SEGAR - Suci Indah Supriyatini (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2025)
Cow's milk is an important source of animal protein for the human body as it provides high protein and a goodgrowth medium for microorganisms. Milk that is milked in an improper way can contain microorganisms thatcan reduce milk quality. One way to see contamination in fresh cow's milk is by Total Plate Count. Commonlyused diluent solutions are Buffer Peptone Water and 0.9% physiological NaCl. The purpose of the study was todetermine whether there is a difference between Buffer Peptone Water and 0.9% physiological NaCl as adiluent solution against bacterial contamination based on the results of TPC examination. This study is anexperimental study with the use of BPW solution and 0.9% physiological NaCl. The results showed that theaverage TPC value of fresh cow milk using BPW solvent in sample 1 was 1.36 x 107 CFU/mL, sample 2 was1.25 x 107 CFU/mL, sample 3 was 1.12 x 107 CFU/mL. The results of the average TPC value of fresh cow's milkusing 0.9% NaCl solvent in sample 1 amounted to 2.75 x 105 CFU/mL, sample 2 amounted to 3 x 105 CFU/mL,sample 3 amounted to 3.65 x 105 CFU/mL. Different solutions affect the results of the calculation of the numberof colonies in each cup counting method. The statistical results of the Paired Sample T-Test test obtained asigma value of sample 1 which is 0.127, sample 2 which is 0.137 and sample 3 which is 0.088 which meansthere is no difference in the TPC test results of fresh cow's milk using BPW and 0.9% physiological NaCl.Keywords: buffer peptone water; physiological NaCl 0.9%; fresh cow milk; total plate count.